A child born with Edward's syndrome: the legal and moral duty to accede to the request for parentage determination. Issue 6 (11th June 2013) - Chan, Tak Kwong; Hui, Edwin; Chung, Brian
Abstract : Advances in medical technology inevitably bring about different kinds of ethical challenges for practising doctors. The following hypothetical case of assisted reproduction is presented as an example. A boy is born with Edward's syndrome following assisted reproduction. The parents suspect that there has been an error of embryo mix-up. They challenge the parenthood and request a genetic test to determine the biological parentage of the neonate. Should the attending paediatrician in this case accede to the request? We argue that the paediatrician has no legal obligation to offer the test, although it might be lawful and ethical to provide the test subject to the outcome of our proposed three-step risk assessment.